2019
DOI: 10.1021/acsaem.8b01905
|View full text |Cite
|
Sign up to set email alerts
|

Toward 3D Thin-Film Batteries: Optimal Current-Collector Design and Scalable Fabrication of TiO2 Thin-Film Electrodes

Abstract: Three-dimensional (3D) thin-film solid-state batteries are an interesting concept for microstorage, promising high footprint capacity, fast charging, safety and long lifetime. However, to realize their commercialization, several challenges still need to be overcome. In this work, we focus on two issues: the conformal coating and the high throughput deposition of thin-film layers. First, to facilitate conformal deposition, a design based on 3D micropillars is chosen. Although such a design has been suggested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…135,[144][145][146][147][148] Thin lms of the organic electrode and inorganic solid-electrolyte materials deposited from gaseous precursors on top of each other is in principle the simplest form of a microbattery, 109,149 andpotentiallyby moving from planar to three-dimensional substrates high footprint capacity can be achieved. 150 In addition, since the ALD/MLD fabricated thin-lm microbattery can be made without any additives it forms the simplest system where the interactions of the layers could in principle be studied in an electrochemical half-cell. This unique possibility has not yet truly challenged, though, leaving exciting possibilities to foreseen future.…”
Section: Mutual Benetsmentioning
confidence: 99%
“…135,[144][145][146][147][148] Thin lms of the organic electrode and inorganic solid-electrolyte materials deposited from gaseous precursors on top of each other is in principle the simplest form of a microbattery, 109,149 andpotentiallyby moving from planar to three-dimensional substrates high footprint capacity can be achieved. 150 In addition, since the ALD/MLD fabricated thin-lm microbattery can be made without any additives it forms the simplest system where the interactions of the layers could in principle be studied in an electrochemical half-cell. This unique possibility has not yet truly challenged, though, leaving exciting possibilities to foreseen future.…”
Section: Mutual Benetsmentioning
confidence: 99%
“…The results of these optimization studies were recently published and are shown in Figure 6. [34] Here, the capacity is plotted as a function of h and l1, with Cv = Cv,2 = 1000 mAh cm −3 , lsse = 100 nm and G = 1. Figure 6 reveals that a high capacity can achieved in two different ways: increasing the aspect ratio (and the pillar density) or increasing the film thickness.…”
Section: Minimizing the Inter-pillar Spacing And Second Electrode Thimentioning
confidence: 99%
“…Analogous to the historical development of transistors (see Moore's law), the roadmap for such 3D thin-film batteries will be the continuous increase in pillar density to enhance the (charging) speed. Adapted with permission from [34] . Copyright 2019 American Chemical Society.…”
Section: Minimizing the Inter-pillar Spacing And Second Electrode Thimentioning
confidence: 99%
“…As a solution for the low capacity of planar thin-film batteries, the concept of 3D thin-film Liion batteries has been introduced. [14][15][16][17] Here, the complete cathode/electrolyte/anode thin-film stack is coated over 3D microstructured current collector substrates. The increased effective surface area increases the actual amount of active material per footprint area.…”
mentioning
confidence: 99%
“…More details on the progress toward the 3D all solid-state thin-film Lithium and Li-ion batteries and the prognosis in capacity of such microbatteries can be found in recent publications of our group. [16][17] Conformal deposition of thin-film electrode materials over microstructured substrates has been shown for e.g. MnO2 and CuSb by electrochemical deposition (ECD) [18][19] and TiO2 by chemical solution deposition (CSD) where conformal coating was demonstrated by spray coating and atomic layer deposition.…”
mentioning
confidence: 99%